The Public Perception of Services at Ophir Health Center After the Termination of the UHC Program - Anggraini, Veronica Cindy; Putri, Sinta Westika (The Future of Education Journal, 2025)
This research is motivated by the changes in the health financing system following the termination of the Universal Health Coverage (UHC) program, which raises questions regarding the community’s perception of health services at Ophir Community Health Center (Puskesmas Ophir). The aim of this study is to analyze the community’s perception of services at Puskesmas Ophir after the closure of the UHC program and to identify the factors that influence these perceptions. The research method used is qualitative with a descriptive approach. The study was conducted in the working area of Puskesmas Ophir, Luhak Nan Duo Subdistrict, West Pasaman Regency. The research informants were members of the community who were former UHC recipients in West Pasaman Regency. Data were obtained through in-depth interviews with service users, observation, and documentation, which were then analyzed using NVivo 15 software. The findings of the study indicate that the community perceives the services at Puskesmas Ophir as still being good despite the termination of the UHC program. Positive perceptions arise due to the consistent quality of services, the friendliness of the staff, and the accessibility of the services.